Religious Soft Power: Definition(s), Limits and Usage - Ozturk, Ahmet Erdi (Religions, 2023)
The following questions can be asked about the role of religion in global politics and discussions of its power position: (1) If religion is used as a soft power resource, how can we define it [...]